The Significance of Subclinical Epileptiform Activity in Alzheimer's Disease: A Review - Csernus, Emoke Anna; Werber, Tom; Kamondi, Anita; Horvath, Andras Attila (Frontiers in Neurology, 2022)
Hyperexcitability is a recently recognized contributor to the pathophysiology of Alzheimer’s disease (AD). Subclinical epileptiform activity (SEA) is a neurophysiological sign of cortical hyperexcitability, however the results of the studies in this field vary due to differences in the applied methodology. The aim of our review was to summarize the results of the related studies aiming to describe the characteristic features and significance of subclinical epileptiform discharges in the pathophysiologic process of AD from three different directions: 1. what SEA is; 2. why we should diagnose SEA; and 3. how we should diagnose SEA. We scrutinized both completed and ongoing antiepileptic drug trials in Alzheimer’s disease where SEA served as a grouping variable or an outcome measure. SEA seems to appear predominantly in slow-wave sleep, and in the left temporal region and to compromise cognitive functions. We clarify using supportive literature the high sensitivity of overnight EEG in the detection of epileptiform discharges. Finally, we present the most important research questions around SEA and provide an overview on the possible solutions. ns.